1966
DOI: 10.1111/j.1745-6584.1966.tb01603.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Ground‐Water Fluctuations Caused by Ocean Tides in Glynn County, Georgiaa

Abstract: The tidal efficiencies of wells tapping the principal artesian aquifer in Glynn County, Georgia decrease with distance from the influencing tidal body and also decrease with well depth. Although the magnitude of water‐level fluctuation of these wells is largely dependent upon the distance to a large tidal body, the time of a high or a low water level in the wells is mainly dependent upon the time of a high or a low tide in a small, nearby tidal body. A modified formula for computing tidal efficiency is develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…This damping effect progressively diminishes the amplitude of piezometric head in the inland direction [Carr and Van Der Kamp, 1969]. Many studies have treated the problem as a one-dimensional analytical solution of piezometric head response to a tidal loading [e.g., Gregg, 1966;Nielsen, 1990;Serfes, 1992] …”
Section: Introductionmentioning
confidence: 99%
“…This damping effect progressively diminishes the amplitude of piezometric head in the inland direction [Carr and Van Der Kamp, 1969]. Many studies have treated the problem as a one-dimensional analytical solution of piezometric head response to a tidal loading [e.g., Gregg, 1966;Nielsen, 1990;Serfes, 1992] …”
Section: Introductionmentioning
confidence: 99%
“…As previous studies have shown (Gregg 1966;Shih et al 2000;Merritt 2004;Zhou et al 2006a), the tidal effects in aquifer water levels commonly occur with semimonthly, diurnal, or semi-diurnal periodicity. Furthermore, the recent studies (Dong et al 2012;AsadiAghbolaghi et al 2014;Zhou et al 2014) also focus on the tidal-induced groundwater level fluctuations.…”
Section: Barometric Efficiency Estimationmentioning
confidence: 90%
“…The average ranges of water levels vary from 0.011 to 0.498 m (minimum in S3, maximum in L6), indicating damping effects occurring in water levels. The ranges of spring tides in the Ariake Sea are 4-5 m, whereas those of neap tides are 1-2 m. The most significant spring-neap tidal effect occurs in L6, with the spring tidal range of 0.671 m and the neap range of 0.352 m. The water level attenuations result from aquifer damping when tidal waves propagate in the aquifer (Gregg 1966;Jacob 1950). Furthermore, the damping efficiency is determined cohesively by the aquifer hydraulic property and the inshore distance of the gauging site.…”
Section: Tidal Effect Analysesmentioning
confidence: 96%
See 1 more Smart Citation
“…The damping effect of the tide when pressure waves propagate in the aquifer can be described by the tidal efficiency (Jacob, 1940;Gregg, 1966), which is defined as the ratio of amplitude of the hydraulic head in the aquifer to amplitude of the tide. From Equations (1b) and (3) the tidal efficiency (TE ) is given as:…”
Section: Theoretical Backgroundmentioning
confidence: 99%